2021
DOI: 10.1186/s40104-021-00633-8
|View full text |Cite
|
Sign up to set email alerts
|

Natural astaxanthin enhanced antioxidant capacity and improved semen quality through the MAPK/Nrf2 pathway in aging layer breeder roosters

Abstract: Background Natural astaxanthin (ASTA) has strong antioxidant properties and has been widely used as a health product to improve human health. However, the effects of ASTA on the reproductive performance of aging roosters have been poorly studied. We aimed to investigate the effects of dietary ASTA on semen quality and antioxidant capacity in aging roosters and to explore the potential mechanism of semen quality change via anti-oxidation defense system. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 56 publications
0
10
0
1
Order By: Relevance
“…p-NRF2 is an important indicator of NRF2 function ( Bellezza et al, 2018 ). Previous studies have shown that astaxanthin enhanced antioxidant capacity and improves semen quality in aged layer breeders through the MAPK/NRF2 pathway ( Gao et al, 2021 ). In our study, the expression of NRF2 and p-NRF2 in the ovary was significantly up-regulated in the experimental groups, indicating that the oxidative stress level in laying hens in the late laying period was alleviated by NRF2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…p-NRF2 is an important indicator of NRF2 function ( Bellezza et al, 2018 ). Previous studies have shown that astaxanthin enhanced antioxidant capacity and improves semen quality in aged layer breeders through the MAPK/NRF2 pathway ( Gao et al, 2021 ). In our study, the expression of NRF2 and p-NRF2 in the ovary was significantly up-regulated in the experimental groups, indicating that the oxidative stress level in laying hens in the late laying period was alleviated by NRF2 .…”
Section: Discussionmentioning
confidence: 99%
“…It has strong antioxidant activity and has clinical applications for the prevention and treatment of cancer, chronic inflammation, atherosclerosis, aging, eye-related disorders, and cardiovascular diseases ( Farruggia et al, 2018 ; Eren et al, 2019 ; Sztretye et al, 2019 ). In poultry, astaxanthin improves male sperm quality by modulating antioxidant enzyme activity ( Gao et al, 2021 ). In vitro studies have revealed that astaxanthin improves bovine oocyte maturation and promotes progesterone production in luteal cells ( Li et al, 2015 ; Kamada et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…They reported that ASTA had an antioxidant effect on the development of cattle embryo 36 . Gao et al observed that 100 mg/kg ASTA increased semen quality and antioxidant activity in a study they conducted in rooster sperm 37 . Comhaire et al gave 16 mg ASTA orally to 30 infertile male individuals for 3 months.…”
Section: © 2022 Canadian Urological Associationmentioning
confidence: 99%
“…ASTA is a precursor of vitamin A, and its biological activities include antioxidant [ 21 ], anti-inflammatory [ 22 ], and anti-apoptotic properties, as well as the inhibition of lipid peroxidation [ 23 ]. Our previous study suggested that dietary ASTA could enhance sperm motility in aging roosters (an increase from 64.40% to 76.23%), which affects the expression of the MAPK/Nrf2 pathway, and reinforce the antioxidant defense system [ 24 ]. Our previous study revealed that sperm concentration and semen volume were also remarkably increased in animals with ASTA supplementation.…”
Section: Introductionmentioning
confidence: 99%